2007
DOI: 10.1165/rcmb.2006-0376oc
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-Related Mechanisms in Hyperoxic Lung Injury in Mice

Abstract: Reduction of glutathione disulfide (GSSG) to glutathione (GSH) by glutathione reductase (GR) enhances the efficiency of GSH-dependent antioxidant activities. However, GR-deficient (a1Neu) mice are less susceptible to acute lung injury from continuous exposure to > 95% O(2) (96 h: 6.9 +/- 0.1 g right lung/kg body versus room air 3.6 +/- 0.3) than are C3H/HeN control mice (10.6 +/- 1.3 versus 4.2 +/- 0.3, P < 0.001). a1Neu mice have greater hepatic thioredoxin (Trx)1 and Trx2 levels than do C3H/HeN mice, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 59 publications
8
63
2
Order By: Relevance
“…Our studies also indicate that TrxR1 is highly enriched in newborn human and mouse airway epithelia, though these findings require confirmation in a greater number of samples. The activation of Nrf2-dependent antioxidant responses on TrxR1 inhibition provides a plausible mechanism for our previous findings of attenuated hyperoxic lung injury in vivo after the TrxR1 inhibition by ATG (38). We speculate that the protective effects of TrxR1 inhibition on hyperoxia-induced lung injury in vivo are likely GSH dependent and mediated via Nrf2.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our studies also indicate that TrxR1 is highly enriched in newborn human and mouse airway epithelia, though these findings require confirmation in a greater number of samples. The activation of Nrf2-dependent antioxidant responses on TrxR1 inhibition provides a plausible mechanism for our previous findings of attenuated hyperoxic lung injury in vivo after the TrxR1 inhibition by ATG (38). We speculate that the protective effects of TrxR1 inhibition on hyperoxia-induced lung injury in vivo are likely GSH dependent and mediated via Nrf2.…”
Section: Discussionsupporting
confidence: 57%
“…Experimental models utilize the hyperoxic exposure of newborn or adult mice to investigate the pathogenesis of BPD or ARDS, respectively. In hyperoxia-exposed adult mice, we have previously shown that ATG pretreatment persistently inhibits TrxR1 and attenuates lung edema and inflammation (38). Though the mechanisms responsible for these effects were unclear, our data suggested that TrxR1 inhibition could be therapeutically beneficial in protecting against oxidant-induced lung injury.…”
Section: Innovationmentioning
confidence: 65%
See 1 more Smart Citation
“…Bcl-2 protein and mRNA levels in the lung were more significantly increased in transgenic mice than in wild type mice (72). (68,78).…”
Section: Hyperoxia Exaggerates Ventilator-induced Cytokine Productimentioning
confidence: 87%
“…Some recent advances have come from the development of mouse models bearing targeted "conditional" alleles of the gene encoding thioredoxin reductase I (TrxR1, also called Txnrd1 or TR1), which can be disrupted in a cell type-or developmental stage-specific manner. Whereas these models are yielding some exciting insights into the Trx and GSH systems in embryonic development, stress responses, toxicology, cancer, and other processes (Bondareva et al, 2007;Branco et al, 2011;Carvalho et al, 2008;Jakupoglu et al, 2005;Mandal et al, 2010;Rogers et al, 2004;Suvorova et al, 2009;Tipple et al, 2007;Zhang and Lu, 2007), the current treatise will emphasize the interplay of these pathways in supporting DNA replication in animal systems. The enormity of the body of literature on the Trx, GSH, and RNR systems precludes an exhaustive review of these materials, and it is my intention to cover these subjects in only a cursory manner to set the backdrop for understanding these systems in the context of DNA replication in animals.…”
Section: Introductionmentioning
confidence: 99%